2012
DOI: 10.1007/s11064-011-0683-z
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative Damage in Muscular Dystrophy Correlates with the Severity of the Pathology: Role of Glutathione Metabolism

Abstract: Muscular dystrophies (MDs) such as Duchenne muscular dystrophy (DMD), sarcoglycanopathy (Sgpy) and dysferlinopathy (Dysfy) are recessive genetic neuromuscular diseases that display muscle degeneration. Although these MDs have comparable endpoints of muscle pathology, the onset, severity and the course of these diseases are diverse. Different mechanisms downstream of genetic mutations might underlie the disparity in these pathologies. We surmised that oxidative damage and altered antioxidant function might cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
59
0
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(64 citation statements)
references
References 50 publications
3
59
0
2
Order By: Relevance
“…Protein carbonylation in skeletal muscle of nonexercised mdx mice Elevated total protein carbonylation levels have been reported in muscle of mdx mice and DMD patients [17,20]. However, the targets Table 3 Identity of proteins whose expression and protein-protein interactions differs in mdx gastrocnemius, in comparison with wild type.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Protein carbonylation in skeletal muscle of nonexercised mdx mice Elevated total protein carbonylation levels have been reported in muscle of mdx mice and DMD patients [17,20]. However, the targets Table 3 Identity of proteins whose expression and protein-protein interactions differs in mdx gastrocnemius, in comparison with wild type.…”
Section: Discussionmentioning
confidence: 99%
“…Studies reported an abnormal oxidative stress in skeletal muscle of DMD patients and mdx mice [17,18]. Indeed, myofibers lacking dystrophin were highly susceptible to oxidant-induced injury [19] and thus, the Contents lists available at ScienceDirect journal homepage: www.elsevier.com/locate/freeradbiomed protein carbonylation level correlated with the degree of the disease [20]. In the absence of dystrophin, oxidative stress acts together with mechanical stress to worsen fiber damage [17].…”
Section: Introductionmentioning
confidence: 99%
“…The increase of oxidative stress in muscular dystrophy, which was acknowledged a long time ago (132,228), has been shown to correlate with the severity of the pathology (274) and is considered to contribute to the pathology of several muscular dystrophies (173). Interestingly, mutations in the antioxidant sepn1 gene cause SEPN1-related myopathy, a different class of muscle disease (14).…”
Section: Muscular Dystrophiesmentioning
confidence: 99%
“…Oxidative stress has been postulated to play an important role in several degenerative conditions (Moosmann and Behl 2002). In the dystrophic muscle, oxidative stress is a potential pathogenetic factor which may determine the severity of the pathology (Kim et al 2013, Renjini et al 2012. In this study, it was shown that DMD and SMD patients present a decrease of SOD activity in the serum without alteration in the others oxidative parameters.…”
Section: Discussionmentioning
confidence: 50%